Central Role of Glucocorticoid Receptors in Alzheimer’s Disease and Depression - Canet, Geoffrey; Chevallier, Nathalie; Zussy, Charleine; Desrumaux, Catherine; Givalois, Laurent (Frontiers in Neuroscience, 2018)
Alzheimer’s disease (AD) is the principal neurodegenerative pathology in the world displaying negative impacts on both the health and social ability of patients and inducing considerable economic costs. In the case of sporadic forms of AD (more than 95% of patients), even if mechanisms are unknown, some risk factors were identified. The principal risk is aging, but there is growing evidence that lifetime events like chronic stress or stress-related disorders may increase the probability to develop AD. This mini-review reinforces the rationale to consider major depressive disorder (MDD) as an important risk factor to develop AD and points the central role played by the hypothalamic-pituitary-adrenal (HPA) axis, glucocorticoids (GC) and their receptors (GR) in the etiology of MDD and AD. Several strategies directly targeting GR were tested to neutralize the HPA axis dysregulation and GC overproduction. Given the ubiquitous expression of GR, antagonists have many undesired side effects, limiting their therapeutic potential. However, a new class of molecules were developed, highly selective and acting as modulators. They present the advantage to selectively abrogate pathogenic GR-dependent processes, while retaining beneficial aspects of GR signaling. In fact, these “selective GR modulators” induce a receptor conformation that allows activation of only a subset of downstream signaling pathways, explaining their capacity to combine agonistic and antagonistic properties. Thus, targeting GR with selective modulators, alone or in association with current strategies, becomes particularly attractive and relevant to develop novel preventive and/or therapeutic strategies to tackle disorders associated with a dysregulation of the HPA axis.